Adverse events generated by acellular dermal matrix in treatment of diabetic foot ulcers: A Literature Review - Torres DÃaz, MarÃa Carolina; Picón Tamayo, Luisa MarÃa; Caraballo MartÃnez, Gilma Jeannette; Serrano Riaño, Julieth Yadira; Vaca-González, Juan Jairo (Revista Cubana de Investigaciones Biomédicas, 2021)
Background: The purpose of this review was to highlight the acquired complications when acellular dermal matrix is grafted in chronic diabetic foot ulcers. Methods: Different information sources, Pubmed, Research and Scielo databases were reviewed to summarize different contributions for the past 20 years. Results: Adverse events reported by application of acellular dermal matrix were infection, seroma, peri-wound erythema, maceration, hematomas, liquefactions, necrosis, gastrointestinal disorder, ischemia, malodor and matrix resorption. Conclusions: The acellular dermal matrix as dermal substitute generates adverse events when treating diabetic foot ulcers; however, there are optimal allografts that did not register adverse events after application. Regardless the adverse events generate by acellular dermal matrix, they may improve the healing process of uninfected, non-ischemic and full-thickness diabetic foot ulcers. In fact, it is evident that the acellular dermal matrix has advantages compared with standard of care.